Analysis of stress in periodontium associated with orthodontic tooth movement: a three dimensional finite element analysis. Issue 16 (6th December 2021) - Jain, Ankita; Prasantha, G. S.; Mathew, Silju; Sabrish, Sharanya
Abstract: It is well known that the initiating factor for the biologic changes is the stress induced in the periodontal tissue; but as of now there is no gauge to measure the stress in the PDL directly. Therefore finite element model can be used to study the stress-strain relation through simulation of the PDL. The aim of the study was to simulate the stress response in the periodontium for different moment to farce ratios induced by tipping, translation, rotation, intrusion, extrusion and root torque by means of finite element method. The three-dimensional finite element model of the mandibular first molar was constructed. The pattern of Von misses stress and the maximum displacement of the mandibular molar was recorded on application of different combination of moment to force ratio. The periodontium was sensitive to changes in the load values. The stress pattern in the periodontal ligament for a lingually directed force without counterbalancing moments showed high concentration at the cervical level of the root. With addition of counter-tipping and counter-rotation moments, a relatively even distribution of stress throughout PDL was obtained. Additionally, high stress concentration was observed on the root surface at the furcation level for forces applied parallel to the long axis. Translation type of tooth movement showed relatively even distribution of the stress in the PDL and makes the tooth less susceptible to root resorption.